Prevalence Suspected Amblyopia (Lazy Eye) at SDN 11 and 17 Kebon Jeruk, West Jakarta 2025 - Hidayat, Dede; Silaen, Desi Hartati; Indrajanti, Mirza (Jurnal MedScientiae, 2026)
Amblyopia or "lazy eye" is a visual impairment due to abnormal visual development in childhood. If not treated early, it can cause permanent visual acuity loss. The main causes are uncorrected refractive errors and strabismus. Routine examinations at school are important to detect and prevent long-term impacts. To determine the prevalence of suspected amblyopia in students of SDN 11 and 17 Kebon Jeruk, West Jakarta, and its distribution based on age, gender, type, and clinical classification of amblyopia. This study used a descriptive analytical design with a cross-sectional approach. Of the 840 students, 792 met the inclusion criteria through total sampling. The examination included visual acuity (Snellen Chart), refractive status (autorefractor), and identification of the type and classification of amblyopia. It was found that 108 children (13.6%) were identified as suspected amblyopia. The proportion of cases was higher in girls (54.6%) than boys (45.4%). The age with the highest number of cases was 10 years (23.1%), followed by 7 years (21.3%). Based on the type, 53.7% were classified as anisometropic amblyopia and 46.3% were isometropic. In terms of classification, the majority (99.1%) were refractive amblyopia and only 0.9% were deprivation amblyopia.